2021
DOI: 10.1101/2021.03.02.433402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic characterization of four novel bacteriophages infecting the clinical pathogenKlebsiella pneumoniae

Abstract: Bacteriophages are an invaluable source of novel genetic diversity. Sequencing of phage genomes can reveal new proteins with potential uses as biotechnological and medical tools, and help unravel the diversity of biological mechanisms employed by phages to take over the host during viral infection. Aiming to expand the available collection of phage genomes, we have isolated, sequenced, and assembled the genome sequences of four phages that infect the clinical pathogen Klebsiella pneumoniae: vB_KpnP_FBKp16, vB_… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…The presence of tRNA genes in phage genomes, especially in virulent phages, is a common phenomenon [87,88]. The discovery of tRNA has been reported for the first time in the genome of the T4 myovirus infecting Escherichia coli, and extensive studies for expression and functionality of T4 tRNA [89] and other phages [87,90,91] have been reported. Some studies have proposed that tRNA-containing phages have a codon bias that diverges from that of the bacterial host, therefore using the tRNAs to compensate for a metabolic difference [91,92].…”
Section: Analysis Of Phage Genomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of tRNA genes in phage genomes, especially in virulent phages, is a common phenomenon [87,88]. The discovery of tRNA has been reported for the first time in the genome of the T4 myovirus infecting Escherichia coli, and extensive studies for expression and functionality of T4 tRNA [89] and other phages [87,90,91] have been reported. Some studies have proposed that tRNA-containing phages have a codon bias that diverges from that of the bacterial host, therefore using the tRNAs to compensate for a metabolic difference [91,92].…”
Section: Analysis Of Phage Genomesmentioning
confidence: 99%
“…The discovery of tRNA has been reported for the first time in the genome of the T4 myovirus infecting Escherichia coli, and extensive studies for expression and functionality of T4 tRNA [89] and other phages [87,90,91] have been reported. Some studies have proposed that tRNA-containing phages have a codon bias that diverges from that of the bacterial host, therefore using the tRNAs to compensate for a metabolic difference [91,92]. Canchaya et al [93] suggested that the presence of tRNA in the phage genome can be correlated with better integration of virulent phages inside the host chromosome.…”
Section: Analysis Of Phage Genomesmentioning
confidence: 99%
“…Klebsiella pneumoniae KP (KP) is a Gram-negative bacillus, which is easy to colonize the upper respiratory tract and intestine of the human body. The detection rate of KP in the pharynx of a healthy population is 1%–6%, and the detection rate of the upper respiratory tract in hospitalized patients is as high as 20%, and the main infection site is the lungs [ 1 , 2 ]. Severe infections are caused when resistance is reduced, and KP is a common conditional pathogen of nosocomial-acquired pneumonia in chronic lung disease patients with diabetes and coma.…”
Section: Introductionmentioning
confidence: 99%
“…S12 and S13). However, sequence similarity (Altschul et al, 1990) and structure-based homology modeling (Kelley et al, 2015) suggest that the phage carries 14 tail fiber proteins (Table 1, gp168, gp196, gp294, gp295, gp300, gp301, gp303, gp304, gp306, gp307, gp308, gp309, gp310, and gp313) instead of the nine previously predicted ones (Bonilla et al ., 2021). These proteins possess putative depolymerizing activity (lyase or hydrolase) and a β-helical fold, which is a hallmark feature for Klebsiella phage depolymerases.…”
Section: Resultsmentioning
confidence: 99%
“…The recently described vB_KpM_FBKp24 (ϕKp24) jumbo myophage encodes at least nine tail fibers containing different depolymerase domains, which suggests an expanded host range. Genomic analysis revealed that ϕKp24 has very limited similarity to any other known phage (Bonilla et al, 2021) and therefore constitutes a new family termed vanleeuwenhoekviridae (ICTV classification). Furthermore, transmission electron microscopy revealed a unique complex structure of tail fibers at the baseplate.…”
Section: Introductionmentioning
confidence: 99%